1964
DOI: 10.3181/00379727-116-29199
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Mice Against Gram-Positive Bacteria with Maytenus laevis and Other RES Stimulants

Abstract: A survey of botanical preparations revealed a number of specimens capable of inducing hyperphagocytic activity in mice ( 1 ) . Judged by effect upon rate of clearance of intravascular carbon( 2,3), the most potent preparation was a suspension of pulverized leaves of a Venezuelan evergreen (Maytenus laevis) .This preparation was interesting because (a) administered intravenously, it accelerated phagocytosis without inducing hepatosplenomegaly, and (b) it showed evidence of activity following oral administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The blockading effects of cholesterol oleate were described by Stuart (19), and thorotrast has been widely used as a blockading agent (20)(21)(22)(23). Zymosan has generally been used as a stimulating agent (24)(25)(26), but has also been shown to cause an initial period of blockade (27), as described here. The stimulating effect of stilboestrol has been described by Nicol and coworkers (28), and our results are in agreement with their observations.…”
Section: Discussionmentioning
confidence: 99%
“…The blockading effects of cholesterol oleate were described by Stuart (19), and thorotrast has been widely used as a blockading agent (20)(21)(22)(23). Zymosan has generally been used as a stimulating agent (24)(25)(26), but has also been shown to cause an initial period of blockade (27), as described here. The stimulating effect of stilboestrol has been described by Nicol and coworkers (28), and our results are in agreement with their observations.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activity, in species of the Genus Maytenus, is related to flavonoids and triterpenes (Zhang et al 2020). The evaluation of the aqueous (infusion and decoction) and alcoholic extracts of the leaves and bark of M. laevis have shown activity against Staphylococcus aureus, Streptococcus pyrogenes, Enterococcus faecalis ATCC 29212 and Pseudomonas aeruginosa ATCC 27853, in vivo and in vitro (Dicarlo et al 1964, Graak & Flemming 2004).…”
Section: Antibacterial and Antiprotozoal Activitymentioning
confidence: 99%
“…Research has shown that extracts of M. laevis induce antibacterial activity due to stimulation of the reticuloendothelial system in experimental animals (Dicarlo et al 1964, Graack & Flemming 1966, Rojas et al 2016.…”
Section: Antibacterial and Antiprotozoal Activitymentioning
confidence: 99%